Nosná železobetonová konstrukce dětského hospice - Kožušník, Přemysl (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Diplomová práce se zabývá návrhem vybraných prvků monolitických a prefabrikovaných částí železobetonové konstrukce dětského hospice. Konkrétně je v práci řešena monolitická základová deska a stěny suterénu s požadavkem na vodonepropusnost těchto konstrukcí. Dále byly z monolitických částí konstrukce řešeny průvlaky, stropní deska nad suterénem a sloup. V práci byl také proveden návrh ramen prefabrikovaného schodiště. Dimenzování prvků bylo provedeno dle ČSN EN 1992-1-1: Navrhování betonových konstrukcí – obecná pravidla a pravidla pro pozemní stavby. Byly provedeny výkresy tvaru dimenzovaných částí konstruce a výkresy výztuže.

The thesis deals with the design of selected elements of monolithic and prefabricated parts of reinforced concrete structure of a children's hospice. Specifically, the thesis deals with the monolithic foundation slab and basement walls with the requirement for watertightness of these structures. Furthermore, the spans, the floor slab above the basement and the column were designed based on the monolithic parts of the structure. The design of the arms of the prefabricated staircase was also carried out. The dimensioning of the elements was carried out in accordance with ČSN EN 1992-1-1: Design of concrete structures - general rules and guidelines for civil engineering. Drawings of the shape of the dimensioned parts of the structure and drawings of the reinforcement were made.
Supporting reinforced concrete structure of the children's hospice
Keywords: bílá vana; základová deska; suterén; vodonepropusnost; stěna suterénu; průvlak; sloup; prefabrikované schodiště; železobeton; stropní deska; dětský hospic; white bath; foundation slab; basement; waterproofness; basement wall; beam; column; prefabricated staircase; reinforced concrete; ceiling slab; children's hospice